2019
DOI: 10.1002/rcm.8406
|View full text |Cite
|
Sign up to set email alerts
|

Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry analysis for characterization of lignin oligomers using cationization techniques and 2,5‐dihydroxyacetophenone (DHAP) matrix

Abstract: Rationale Effective analytical techniques are needed to characterize lignin products for the generation of renewable carbon sources. Application of matrix‐assisted laser desorption/ionization (MALDI) in lignin analysis is limited because of poor ionization efficiency. In this study, we explored the potential of cationization along with a 2,5‐dihydroxyacetophenone (DHAP) matrix to characterize model lignin oligomers. Methods Synthesized lignin oligomers were analyzed using the developed MALDI method. Two matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…Mass spectra of PCTs recorded on the addition of lithium, sodium, and potassium salt solutions to test samples were investigated ( Table 2). The level of concentrations of cationizing agents and their ratio to analyte concentrations were chosen based on the published data on the study of plant samples by MALDI mass spectrometry [27].…”
Section: Resultsmentioning
confidence: 99%
“…Mass spectra of PCTs recorded on the addition of lithium, sodium, and potassium salt solutions to test samples were investigated ( Table 2). The level of concentrations of cationizing agents and their ratio to analyte concentrations were chosen based on the published data on the study of plant samples by MALDI mass spectrometry [27].…”
Section: Resultsmentioning
confidence: 99%
“…LDI-MS experiments indicated that the presence of specific peaks, the way in which the peaks were grouped, and the global shape of the spectrum reflected the global structure of lignin oligomers [73]. LDI-MS analysis revealed a wide mass distribution of lignin oligomers [74,75]. However, the experimental conditions allowed the analysis of monocharged species with low fragmentation.…”
Section: Methodsmentioning
confidence: 99%
“…Lignin molecule weight has also been investigated by mass spectroscopy, particularly matrix-assisted laser desorption/ ionization mass spectrometry (MALDI-MS). However, the heterogeneous nature of lignin and the challenge of ionizing all fractions equally severely limit the use of this technique for accurate characterization of lignin [32].…”
Section: Trends Trends In In Chemistry Chemistrymentioning
confidence: 99%